Association Between Personality Traits Toward Culture Shock Among Indonesian Caregiver in Japan Under Economic Partnership Agreement - Yektiningsih, Erwin; Risnasari, Norma; Tri Wijayanti, Endah (Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Background: Among Indonesian nurses who worked in Japan under Economic Partnership Agreement (EPA). They were placed in hospitals as nurses and nursing homes as caregivers. They experience cross-cultural tend to culture shock because of the personality traits needed socio-cultural to adaptations skills to live new environment.Purpose: This study aimed to increase professionally among Indonesian nurses placement job in Japan with enhancing adequate personality traits for adaptation cross-cultural live and health facility job in Japan that can preventive culture shock.Methods: This study used a cross-sectional approach with a non-probability sampling method. The population study was 307 among health professionals migration Indonesian in Japan, and obtained a sample of 180 respondents of Indonesian caregiver in nursing home Japan, that passing the National Board Examination (NBE) and have not. Selected using a random sampling technique. The data were collected using questioner. Data analysis used a contingency coefficient.Results: The results of research culture shock participants were 17% and normal 83%. This showed study extraversion have a significant association with culture shock (? value = 0. 042) and openness (? value = 0.109), conscientiousness (? value = 0.518), agreeableness (? value = 0.213), neuroticism (? value = 0.592) were not a significant association with culture shock.Conclusion: The nursing institutions plants to curriculum containing material for increasing nursing resources study cross-cultural skills in an abroad workplace to avoid culture shock who need very good mentally with increase competence of reinforcing positive personality traits